2021
DOI: 10.1097/xeb.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing implementation of the GLA:D Back, an educational/exercise intervention for low back pain: a mixed-methods study

Abstract: Introduction and aims: Guidelines for low back pain (LBP) management recommend patient education and exercises. GLA:D Back, a structured group-based patient-education exercise program for LBP, facilitates evidence-based care implementation. This study aimed to inform on the implementation processes, assessing clinician-related factors. Objectives were to describe profiles of implementers and nonimplementers by demographics, and responses to the tailored version of the Determinants of Implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The previous studies have applied the DIBQ-t in evaluating the expectations of the implementation process in profession-specific interventions. 40 , 41 In the Swedish study, facilitating role of most domains of DIBQ-t was reported. 41 The Danish study investigated clinician-level factors related to implementing evidence-based care for LBP patients in primary care using DIBQ-t and qualitative assessments.…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies have applied the DIBQ-t in evaluating the expectations of the implementation process in profession-specific interventions. 40 , 41 In the Swedish study, facilitating role of most domains of DIBQ-t was reported. 41 The Danish study investigated clinician-level factors related to implementing evidence-based care for LBP patients in primary care using DIBQ-t and qualitative assessments.…”
Section: Discussionmentioning
confidence: 98%
“…Qualitative data was valuable in understanding why competence of knowledge and skills were reported both by clinicians that implemented and by those that did not implement the intervention after evidencebased training. The study indicated that training alone is insu cient for implementation (51).…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 95%
“…The authors are not aware of other tools that are intended to be used for the research on implementation of multiprofessional rehabilitation interventions. The previous studies have applied the tailored version of DIBQ in evaluating the expectations of the implementation process (51,52). In the Swedish study, facilitating role of most domains of DIBQ-t was reported (52).…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…However, implementation is not straightforward. Some clinicians do not buy in on the underlying cognitive-behavioural principles, and some of those who do, find it challenging to deliver (Ris et al, 2023). Also, the patient receipt indicates potential challenges in targeting individual needs ( Joern et al, 2022).…”
Section: What Does This Study Add?mentioning
confidence: 99%